2014
DOI: 10.1016/j.ijmyco.2014.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Indian TrueNAT micro RT-PCR device with GeneXpert for case detection of pulmonary tuberculosis

Abstract: To evaluate the performance of TrueNAT (RT Micro PCR device) assay in comparison with GeneXpert on sputum samples from pulmonary cases of tuberculosis. 274 samples were processed to detect MTB by ZN smear examination, MGIT culture and molecular methods that included RT-PCR (ABI 7500 & TrueNAT) and GeneXpert for case detection of TB. The overall performance of the test with MGIT(Mycobacterium Growth Indicator Tube) culture as gold standard, sensitivity of smear, RT PCR/TrueNAT and Genexpert was 61.5% (CI:53.3-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 13 publications
2
39
0
1
Order By: Relevance
“…In this study, less than half who advised bacteriological diagnosis asked for both rapid and culture tests; some used culture methods alone which, although accurate, are time consuming and delay diagnosis. Use of rapid molecular techniques like Xpert MTB/RIF is useful to prevent delay but it only detects resistance to rifampicin [ 35 , 36 ]. Presence of resistance to other antibiotics goes undetected and it does not help in formulating individualised regimen.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, less than half who advised bacteriological diagnosis asked for both rapid and culture tests; some used culture methods alone which, although accurate, are time consuming and delay diagnosis. Use of rapid molecular techniques like Xpert MTB/RIF is useful to prevent delay but it only detects resistance to rifampicin [ 35 , 36 ]. Presence of resistance to other antibiotics goes undetected and it does not help in formulating individualised regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the Truenat MTB test (Molbio Diagnostics, India) [19] undertaken in India found sensitivity and specificity to be similar to that of the Xpert MTB/RIF assay [20,21], whereas a study using EasyNAT in Tanzania reported high specificity (100%) and a sensitivity compared with culture of 66.7%, with 10% of smear-negative cases found to be positive [22]. A study from China on the EasyNAT Diagnostic Kit (Ustar Biotechnologies, China) [23] using processed sputum reported sensitivity and specificity of 84% and 98%, respectively.…”
Section: Nucleic Acid Amplification Testsmentioning
confidence: 99%
“…However, it has poor sensitivity (~70%) and is dependent on the skill of the personnel performing the test. 7,10 If the result of the AFB staining is negative but the clinical suspicion is high, culturing should be performed to test for M. tuberculosis. 4,22 Culturing is a golden standard in the diagnosis of M. tuberculosis infection.…”
Section: Diagnosis: Methods and Samplesmentioning
confidence: 99%
“…The assay uses quantitative real-time polymerase chain reaction (qRT-PCR) to detect both M. tuberculosis and rifampicin resistance within 2 hours. [5][6][7] This review discusses the basic concept of TB, the different types of diagnostic methods, and the specimens for TB diagnosis.…”
mentioning
confidence: 99%